AgriTech4Egypt Acceleration Program and Demo Day Report - Zaccari, Claudia (Bioversity International and International Center for Tropical Agriculture, 2024)
The AgriTech4Egypt Innovation Challenge 2024 is a project designed to empower talented innovators and accelerate the development, deployment, and adoption of early-stage agri-tech solutions that can create a more sustainable, efficient, and climate-resilient agriculture in Egypt, while aligning with the country’s 2030 Sustainable Agricultural Development Strategy and Sustainable Development Goals (SDG). This report focused on the Acceleration Program and Demo Day phases.